Особливості змісту та здійснення права віртуальної власності - Некіт, Катерина Георгіївна; Некіт, К. Г.; Nekit, Kateryna H. (Одеса, 2019)
У статті проаналізовано можливість визнання права віртуальної власності як особливого виду права власності. Досліджено правову природу права віртуальної власності, особливості його змісту, здійснення та захисту. Проаналізовано співвідношення прав провайдерів / розробників платформ та користувачів. Надано оцінку поняттю «цифрова сила» та визначено напрями її обмеження з метою недопущення зловживань з боку провайдерів. Визначено можливості володільців віртуального майна здійснювати та захищати свої права.

In this article the possibility to qualify the virtual property right as a special type of the property rights is analysed. It is possible to use such an approach in Ukrainian law as the concept of “thing” according to the Ukrainian legislation is treated widely, and includes not only objects of a material world, but also incorporeal things. Therefore, the Ukrainian concept of the property right allows to extend the existing regime of the property right to virtual assets. Not only the object of the virtual property right (which will always be incorporeal things) will have its specific. The bases for the virtual property right, its content and protection of the virtual property right will also have specifics. In the article the legal nature of the virtual property right is also investigated. The conclusion is drawn that the virtual property right is the real right as answers all principles of the real right. The specifics of the content of the virtual property right are defined. Unlike the traditional possession, digital possession is not exclusive, as several persons can own an object at the same time (that is to have control over this object). The right to use the digital property also has its specifics. Such right has to be provided by provider. The provider also has to provide a constant possibility to have an access to the object which belongs to an individual. The right to dispose of digital property can be limited by provider and by properties of the platform itself that also needs to be considered. Ensuring protection of virtual property requires an assistance of provider as well. Thus, the right of virtual property has the dual nature. On the one hand, it is absolute – in the relations between the virtual owner and the third parties. On the other hand, in the relations with provider it has relative character. In the article the balance of the rights of providers/developers of platforms and users is analyzed. The concept “digital force” is analysed and some directions of its restriction for the purpose of prevention of abuses on the part of providers are defined. Possibilities of virtual property owners to protect their rights are defined. In particular, an opportunity to use actions “in rem” for protection of virtual property is analysed.
Некіт К. Г. Особливості змісту та здійснення права віртуальної власності / К. Г. Некіт // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Одеса, 2019. – Вип. 32. – С. 86-92.
Keywords: віртуальна власність; право власності; віртуальне майно; цифрове майно; цифрова сила; внутрішньоігрові предмети; ігрові акаунти; провайдери; користувачі; virtual property; property right; digital property; digital force; in-game objects; game account; providers; users; Research Subject Categories::LAW/JURISPRUDENCE; Research Subject Categories::TECHNOLOGY